Ethanol Fuel Production Through Microbial Extracellular Enzymatic Hydrolysis And Fermentation From Renewable Agrobased Cellulosic Wastes - MIR NAIMAN ALI; MAZHARUDDIN KHAN MOHD; MAJID MOHIUDDIN (International Journal of Pharma and Bio Sciences, 2011)
In the present work renewable agricultural cellulosic wastes groundnut hulls and rice husks were selected for production of bioethanol fuel. Two locally isolated microorganisms cellulase producing fungus Aspergillus niger and ethanol producing Saccharomyces cerevisiae were employed for saccharification and fermentation respectively. Substrates were enzymatically saccharified by using A. niger followed by addition of S. cerevisiae for fermentative production of bioethanol. Two methods of fermentation i.e. stationary and shaking were adopted. High yield of ethanol was obtained from groundnut hulls in stationary fermentation method.